Cluster Computing Analysis Based on Beowulf Architecture - Purnawansyah Purnawansyah; Ramdan Sastra (International Journal of Computing and Informatics (IJCANDI), 2016)
The need for computing speed in data processing is in high demandindicated by the increasing data processing in many companies.Aviation companies, for instance, show the growing number ofpassengers daily. The data processing for a big number of customersrequires supercomputer technology at the cost of exponential fund.Therefore, the technology able to process big data with low cost isnecessary. This research has improved a cluster computer which canprocess data with a big capacity processing that is generally cannotbe processed using one computer. Cluster computer is built usingBeowulf cluster architecture using Linux Debian operating systemand SSH, NFS, MPI library and GANGLIA services. The result ofthis research is a cluster computer prototype which is able to process38.000x38.000 matrix calculation data. In the first testing, thecomputer was able to work for a maximum of 30.000x30.000 matrixcalculation whereas cluster computer can process up to38.000x38.000 matrix size. This result indicates that the designedcluster computer is successful to calculate big data with a lowcomputer specification. The further improvement can be applied in amore complicated computer calculation process and bigger data.